2022
DOI: 10.1590/1806-9061-2021-1618
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Factors Affecting the Price of Broiler Chicken in Turkey Using the Boosting Regression Method

Abstract: Investigating the factors that affect broiler chicken prices in Turkey is vital for understanding market formation. The parameters and factors likely to influence the price of broiler chicken were analyzed for the period between 2010-2020 in Turkey. The study adopted the boosting regression model to predict the correlation between broiler chicken consumer price and variable factors like broiler feed, corn, soybean meal, wheat prices, the dollar exchange rate, producer price index (PPI), and agricultural PPI. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…These values were considered statistically significant at a significance level (α) of less than 0.01. Furthermore, they reflected the relationship between strong and very strong broiler price in a specific region compared to the national level [ 48 ]. The coefficient value ( β 1 ) was below one ( β 1 < 1) for the time periods before, during, and after COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…These values were considered statistically significant at a significance level (α) of less than 0.01. Furthermore, they reflected the relationship between strong and very strong broiler price in a specific region compared to the national level [ 48 ]. The coefficient value ( β 1 ) was below one ( β 1 < 1) for the time periods before, during, and after COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that 40% of the variations in corn prices were transmitted to chicken prices, the price transmission between the markets was unidirectional and the corn price seemed to be weakly exogenous. Arikan et al (2022) analysed the parameters and factors likely to influence the price of broiler chickens in Turkey and concluded that chicken prices were affected by the raw material prices for feed. Xu et al (2011) examined the vertical price relationship between upstream and downstream products in China's layer industry chain by using cointegration tests, error correction models and finite distributed lag models, and they found that the influence of corn and feed prices on egg prices was still stronger than that of egg-laying chicken prices.…”
mentioning
confidence: 99%